Prarancangan PabrikEtilen Glikol Dari Etilen Oksida Dan Air Dengan Proses Hidrasi Non Katalitik Kapasitas 230.000 Ton/Tahun - Trisnani, Ika Anik; , Rois Fathoni, S.T. M.Sc. Ph.D; , Ir. Herry Purnama, M.T., Ph.D (2015)
Ethylene glycol or EG is an organic compound that is colorless, odorless, and intangible fluid. Generally, ethylene glycol is used for extra fiber in polyester, PET containers used materials, antifreeze and coolant in the engine. In Indonesia in general and commercial, ethylene glycol is used as raw material for the textile industry (polyester) amounted to 97.34% and 2.66% is used as raw material for the manufacture of paints addition, liquid glue, solvent, printing ink, ink in the pen , cosmetics, and anti-freeze materials. This need is met by PT Polychem Tbk while shortcomings met by importing from different countries. Plant design of ethylene glycol from ethylene oxide and water with non-catalytic hydration process capacity of 230,000 tons/year is planned to be established in 2025 to meet the needs of ethylene glycol in Indonesia, thereby reducing the number of imports. Besides the raw materials and the location in Tangerang, Banten area of 22,000 m2 and with 184 employees strongly supports the establishment of this factory. Plant design of ethylene glycol using raw materials such as ethylene oxide and excess water, with a mole ratio of 1:20. Production capacity of 230,000 tons/year is planned to operate for 330 days per year. The process of making ethylene glycol is carried out in a plug flow reactor continuously without using a catalyst. In the reactor, the process of ethylene glycol maintained that take place in the liquid phase, irreversible, exothermic, and non-isothermal adiabatic temperature and pressure 190C-130,36C up to 18 atm. Conversion achieved was 99.8% with 91.8% selectivity of ethylene glycol. By products produced in the form of diethylene glycol and triethylene glycol. In the process of ethylene oxide are needed as much 24557.451 kg / hour and as much water as 201,596.7468 kg / hour. The products produced in the form of ethylene glycol as 29040.4040 kg / hour. Utilities include water provision process support for 753,155.1632 kg/h obtained from Tangerang Cisadane river water, the provision of saturated steam at 46,768.378 kg/hr of fuel boiler using fuel oil in the form of 12,071.44 L/h, the demand for electricity 2 kW of 2,903.41 obtained from the PLN and a generator set as a backup. Factory ethylene glycol using a fixed capital of Rp 1,034,051,035,025,- and working capital of Rp 1,939,783,918,227, -. Based on the economic analysis of the feasibility of establishing a factory, then the ethylene glycol plant is profitable and worth is established. Profits earned before taxes was Rp 680.800,422.474,- per year after taxes 30% profits reached Rp 476 560 295 732,- per year. Percent Return On Investment (ROI) before tax after tax 65.84% and 46.09%. Pay Out Time (POT) before tax for 1.32 years and 1.78 years after tax. Break Even Point (BEP) is 49.69%, and Shut Down Point (SDP) amounted to 37.58%. Discounted Cash Flow (DCF) accounted for 24.69%.